Burnout status of healthcare workers in the world during the peak period of the COVID-19 pandemic - Ulfa, Maria; Azuma, Momoyo; Steiner, Andrea (Frontiers in Psychology, 2022)
During the COVID-19 pandemic, healthcare workers have a high workload and have been exposed to various psychosocial stressors. This study aimed to evaluate health workers during the COVID-19 pandemic in the world. The method used in this research is qualitative with a literature review approach. The data sources in this study were taken from the Scopus database using the keywords "health workers," "burnout," AND "coronavirus" from the time range of 2020 to April 25, 2022. From the determination of the time range, 150 documents emerged. This study revealed that the Pearson correlation between total burnout scale scores on healthcare workers, professionals, exhaustion, mental, stress, personal, depression, symptoms, emergency, system, job, and impact indicated that overall burnout scores were associated with depression and anxiety. Stress symptoms had correlation values ranging from 0.84 to 0.73. Job burnout had a significant relationship with exhaustion at 0.89; depression r = 0.73), impacting a score of 0.66. At the same time, the fulfillment of professional and interpersonal disengagement showed a Pearson correlation between the total burnout scale scores on health workers, professionals, exhaustion, mental, stress, personal, depression, symptoms, emergency, system, job, and impact. Overall, the participants in health care workers worldwide experienced high levels of psychological distress. We also found that health workers directly in charge of dealing with COVID-19 pandemic patients were more likely to experience depression, stress, and burnout than health staff who were not personally involved in medical work. Furthermore, this study will be a follow-up study using the Work Ability Index (WAI) to measure work ability and work satisfaction. As a primary goal, the abstract should render the general significance and conceptual advance